Characterization of thermoset biopolymer in thermoplastic of low and high density polyethylene upon uv irradiation - Mohd Salim, Nurul Syamimi (2017)
As the economy achieves global status, many factors regarding the competitiveness of a nation come under investigation. More recently, together with important areas such as technology advancement and technology transfer, issues related to sustainable development and environment preservation are receiving increasing attention from the world community. Blends of BioPolymer (BP) and thermoplastic polyethylene (LDPE and HDPE) may contribute to make recycling more economically attractive. In this study, the monomer is mixed with flexible isocynate as a crosslinker, known as BioPolymer (BP). The BP were hand mixed with LDPE or HDPE with propotion ratio of 5%, 10%, 15%, 20%, 25% and 30%. wt/wt of thermoplastic. The melt flow index (MFI) were indicated that the processing temperature is the same for both blends which is 190 °C. The aim of this work is to fabricate and study the processibility of BP/LDPE and BP/HDPE blends using injection molding. Futhermore, Ultra-violet (UV) Accelerated weathering test up were conducted at 500 hours, l 000 hours, 1500 hours, 2000 hours, 2500 hours and 3000 hours. The blends yielded tensile strength, percentage of elongation at break and young's modulus is very dependent on their composition ratio of BP with thermoplastic. The tensile strength increased at 500 hours UV irradiation exposure with BP/LOPE is 10.55 Mpa. This is attributed from further crosslink between BP and thermoplastic LDPE. With the BP/LOPE is 67.64 % which diferent from BP/HDPE with the highest elongation of 53.09 % on virgin HOPE. While elongation at break and young's modulus is found to decrease with increases of UV irradiation hours. The decrement of tensile strength and young's modulus after UV exposure is due to the occurrence of the chain breaking process ( chain scission) of carbon-carbon backbone as a result of photo-oxidation. In conclusion, BP content and UV irradiation time play significant roles in controlling mechanical properties of the BP-blended with LDPE and HOPE synthetic polymer, thus providing the opportunity to modulate polymer properties